2023
DOI: 10.1002/sd.2678
|View full text |Cite
|
Sign up to set email alerts
|

Community resilience implications for institutional response under uncertainty: Cases of the floods in Wayanad, India and the earthquake in Port‐au‐Prince, Haiti

Abstract: While trajectories of community resourcefulness, solidarity, and mutual trust during and following environmental crises are abound in the literature, how these trajectories are taken into consideration and influences spatial planners, humanitarians and decision makers working under uncertainty remains under documented. Our article explores the concept of community resilience in action to illustrate where community resilience in action is supported, hindered or ignored by the state and non‐state organizations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In Wayanad community resilience in Kerala India, revealed that resilience influenced by existing bonding, bridging and bridging social capital (Koshy & Smith, 2023). Our study found that the role of social capital is critical in dealing with the challenges of environmental change due to mining activities.…”
Section: The Role Of Social Capitalmentioning
confidence: 68%
“…In Wayanad community resilience in Kerala India, revealed that resilience influenced by existing bonding, bridging and bridging social capital (Koshy & Smith, 2023). Our study found that the role of social capital is critical in dealing with the challenges of environmental change due to mining activities.…”
Section: The Role Of Social Capitalmentioning
confidence: 68%
“…Koshy and Smith (2024) describe how local community resilience came into action in Wayanad (India) following the 2018 and 2019 floods, and in Port‐au‐Prince (Haiti) following the 2010 earthquake. They provide insights on the social responsibility, solidarity, mutual trust, and cooperation by which community resilience came into action, and on how these processes were undermined by the local root causes of disasters.…”
Section: The Local Community Dimension Of Resilience In Societymentioning
confidence: 99%
“…They investigate and learn about the perceptions and experiences of these communities of CC risks and impacts and of climate action policies. These two papers highlight the relevance of an intersectional approach to disaster risks and impacts, and of enhancing community resources and community-led initiatives for inclusive and effective DRR, climate action, and community resilience-building policies and projects Koshy and Smith (2024). describe how local community resilience came into action in Wayanad (India) following the 2018 and 2019 floods, and in Port-au-Prince (Haiti) following the 2010 earthquake.…”
mentioning
confidence: 99%